High frequency repetitive transcranial magnetic stimulation of the left dorsolateral prefrontal cortex for methamphetamine use disorders: A randomised clinical trial - Su, Hang; Zhong, Na; Gan, Hong; Wang, Jijun; Han, Hui; Chen, Tianzhen; Li, Xiaotong; Ruan, Xiaolu; Zhu, Youwei; Jiang, Haifeng; Zhao, Min (Drug and alcohol dependence, 2017)
•rTMS of left dorsolateral prefrontal cortex (DLPFC) could reduce cue-induced craving for methamphetamine.•rTMS of left DLPFC could improve cognitive function of methamphetamine users.•rTMS had no severe negative effects on cognitive function in methamphetamine –addicted patients. Repetitive transcranial magnetic stimulation (rTMS) is a brain stimulation and modulation electrophysiological technique, it can change cortical excitability of target brain region, modulate neuron plasticity and brain connections. Previous researches indicated that rTMS could reduce cue-induced craving in drug addiction. In this study, we employed real and sham rTMS of the left dorsolateral prefrontal cortex (DLPFC) to test whether it could reduce cue-induced craving for methamphetamine (MA) and influence cognitive function in a randomised clinical trial. Thirty MA-addicted patients were randomized to receive 5 sessions of 8min sham or 10Hz rTMS to the left DLPFC. Subjects rated their craving at baseline, after exposed to MA-associated cues and after rTMS sessions. Real rTMS over the left DLPFC reduced craving significantly after 5 sessions of rTMS as compared to sham stimulation. Furthermore, real rTMS improved verbal learning and memory and social cognition in MA-addicted patients. The present study suggests that 10Hz rTMS of the left DLPFC may reduce craving and have no negative effects on cognitive function in MA-addicted patients, supporting the safety of rTMS in treating MA addiction.